High value-added compounds from fruit and vegetable by-products - Characterization, bioactivities, and application in the development of novel food products - Trigo, João P.; Alexandre, Elisabete M. C.; Saraiva, Jorge A.; Pintado, Manuela E. (Critical reviews in food science and nutrition, 2020)
Fruit and vegetable processing industry is one of the relevant generators of food by-products, which display limited commercial exploitation entailing economic and environmental problems. However, these by-products present a considerable amount of dietary fiber as well as bioactive compounds with important biological activities such as antioxidant and antimicrobial properties. Therefore, the international scientific community has considered the incorporation of their extracts or powders to preserve or fortify food products an area of interest, mainly because nowadays consumers demand the production of safer and health-promoting foods. In the present review, several statistical and other relevant data concerning the increasing generation of fruit and vegetable by-products (FVB) are critically analyzed and presented. Next, a special focus is given to the chemical characterization and bioactivities (namely antioxidant and antimicrobial properties) of several FVB. Lastly, an in-depth review with recent studies (briefly compiled) about the incorporation of fruit and vegetable processing wastes in animal, dairy, beverages, and bakery products, among others is provided.